Behind the Mexican mountains - Zingg, Robert M. (Robert Mowry), 1900-1957 (University of Texas Press, 2001)
The author, a renowned anthropologist, wrote this personal travelogue of his sojourn among the Tarahumara Indians in 1930. The book, unpublished in his lifetime, describes the landscape, people, traditions, language, and archaeology of the Chihuahua, Mexico region.